STABILITY-INDICATING HPTLC METHOD FOR ESTIMATION OF VALACYCLOVIR HYDROCHLORIDE IN BULK AND PHARMACEUTICAL DOSAGE FORM IN PRESENCE OF ITS ALKALINE HYDROLYSIS DEGRADATION PRODUCT - PATIL PALLAVI M; WANKHEDE SAGAR B; CHAUDHARI PRAVEEN.D (International Journal of Pharma and Bio Sciences, 2014)
A novel and quick high-performance thin-layer chromatographic method -densitometric method was developed and validated for quantitative determination of Valacyclovir Hydrochloride. Chromatographic separation of the drugs was performed on precoated silica Tab 60 F254 Merck plates using Toluene: Methanol: Diethylamine (8:1:1 v/v/v).as a mobile phase. A TLC scanner set at 254 nm was used. Valacyclovir Hydrochloride and degradant were satisfactorily resolved with Rf values of 0.28 ± 0.05, 0.65 ±0.05. The method had an accuracy of 99.85% of Valacyclovir Hydrochloride was validated according to ICH guidelines. The percentage recovery ranges from 99-101%. Force degradation of drugs in hydrolysis,oxidation photolysis and thermal stress as per ICH guideline.The drug showed instability in oxide and Heat and Oxide while it remained stable in neutral conditions. The proposed HPTLC method was utilized to investigate of alkaline degradation of VAL.